CONTINUOUS CONDUCTION OF IMPULSES IN PERIPHERAL MYELINATED NERVE FIBERS - Laporte, Y. (The Rockefeller University Press, 1951)
1. Conduction of impulses in peripheral myelinated fibers of a nerve trunk is a continuous process, since with uninjured nerve fibers: (a) within each internodal segment the conduction time increases continuously and linearly with increasing conduction distance; (b) the presence of nodes of Ranvier does not result in any detectable discontinuity in the conduction of the impulse; (c) the ascending phase of the spike always has an S shape and never presents signs of fractionation; (d) the shape and magnitude of the spike are constant at all points of each internodal segment. 2. Records have been presented of the external logitudinal current that flows during propagation of an impulse in undissected single nerve fiber (Fig. 6). 3. Propagation of impulses across a conduction block occurs with a readily demonstrable discontinuity.